Marginal Analysis: An Economic Procedure for Selecting Alternative Technologies/Practices - Edward A. Evans (EDIS)
The purpose of this article is to outline a simple economic procedure, based on the economic principles of marginal analysis, to assist the researchers in decision making. It was made popular at CIMMYT (Perrin, et al., 1988) and is summarized in the article. CIMMYT is the acronym for Centro Internacional de Mejoramiento de Maiz y Trigo (International Maize and Wheat Improvement Center), located in Mexico. This is EDIS document FE565, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published June 2005.